If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5u-2u=3
We move all terms to the left:
5u-2u-(3)=0
We add all the numbers together, and all the variables
3u-3=0
We move all terms containing u to the left, all other terms to the right
3u=3
u=3/3
u=1
| 2(y-6)=3y+-2-y | | x+7=2x+19+80 | | 11=18x+5 | | 65 k=−20 | | z^2+4z-8=0 | | 3(p=2)=-30 | | -12/5x+26/5=6 | | 6-10(5y+7)=150 | | 4x+2=0x+3 | | 6x+1+4x=21 | | 19-9x=22 | | x-6=2x-8=10 | | 0x=70x+60 | | 0x/10=7x+6 | | 11x-2/3=6/7 | | 11=3+v/2 | | 5x/10(7-7)=7x+6 | | a*3+8=12 | | 9x-62=5x-2 | | 7x/11+11=5 | | 5x-12=-5 | | 25x+10=32x-18 | | 1=v22 | | b4=24 | | 77 = 7 y | | 2x+180=48-3x | | (3/5)=(x/12) | | -10x²+19x+15=15 | | 12+x/5=16 | | (x+3/4)=x-12 | | 2x+9=4x–3 | | 16x-6+4=9x+7 |